Green synthesis of porous Cu2ZnSnS4/g-C3N4 heterostructured for promoted photocatalytic degradation of trichloroethylene. Issue 8 (15th April 2022) - Mkhalid, Ibraheem A.; Mohamed, Reda M.; Alhaddad, Maha; Basaleh, Amal; Al-Hajji, L.A.; Ismail, Adel A.
Abstract: Accelerating the photo-induced carrier separation in semiconducting materials under visible-light exposure is a great challenge in effective organic pollutant degradation. Herein, a mesoporous Cu2 ZnSnS4 /g-C3 N4 heterojunction was synthesized through a facile sol-gel approach with hard and soft templates leading to a high-surface-area material. TEM analysis showed spherical Cu2 ZnSnS4 nanocrystals (5 nm in diameter) with a high and uniform distribution on the g-C3 N4 nanosheets. The Cu2 ZnSnS4 /g-C3 N4 photocatalyst (3%) showed photocatalytic trichloroethylene (TCE) degradation to Cl − and CO2 of approximately 100% in an aqueous medium. The optimal rate for this photocatalyst was approximately 7.754 μmol L −1 ·min −1, which was 4 and ∼5.75 folds higher than that of bare Cu2 ZnSnS4 and g-C3 N4, respectively. Moreover, the apparent rate constant of 3% Cu2 ZnSnS4 /g-C3 N4 was 7.6 and 4.1 times higher than that of bare g-C3 N4 and Cu2 ZnSnS4, respectively. Recycling experiments confirmed that the Cu2 ZnSnS4 /g-C3 N4 photocatalyst exhibited remarkably stable photocatalytic activity and could be recycled five times. This work provides a novel insight into the design and preparation of visible-light-based photocatalysts with high and stable photocatalytic efficiency.